Virtual space and popular movement in Algeria - بوبكر الصديق بن شويخ (International Journal of Social Communication, 2021)
This paper; focuses on the important role of social media in promoting freedom and the exercise of the right of expression; within the Algerian community, especially because Algerian society sees social networks as an extension of "bourgeois public space", based on criticism and accountability So the aim of this research is to analyze and critique the discourses of Algerian digital communication platform users, in light of the social and political transformations that Algeria is currently witnessing